PENGARUH PENERAPAN BRANCHLESS BANKING DAN E-BANKING TERHADAP KINERJA KEUANGAN SEKTOR PERBANKAN DI INDONESIA - Ketut Tanti Kustina; Yunike Wulandari Wulandari Sugiarto (Jurnal Ilmiah Akuntansi & Bisnis, 2020)
This study aims to determine the effect of the implementation of branchless banking and e-banking on the performance of Indonesian banks. This type of research is quantitative by using a population of banking companies in Indonesia which are listed on the Indonesia Stock Exchange in 2016 to 2019. Sampling uses a purposive sampling technique. The analytical method used is multiple linear regression analysis. The results of this study indicate that the application of branchless banking has not significant effect on the performance of Indonesian banks and the application of e-banking has a positive and significant effect on the performance of Indonesian banks. Keywords: Branchless Banking, e-Banking, and Indonesian Banking Performance